Optimization study of a multi-heat source coupled bathing hot water system - Yunxin Huang; Jinghui Luo; Yongchang Zhou; Xiaoxuan Wu; Nianchen Wang; Shicheng Xin; Changjian Zhang (Case Studies in Thermal Engineering, 2024)
To reduce the operational energy consumption of a compressed air system coupled with a solar and air-source heat pump hot water system, a model was established using TRNSYS, and the Taguchi method was employed to design experiments for four factors influencing the system's energy consumption. The main effects and relevant statistical analyses of the experimental results revealed that the key factors influencing the system's energy consumption, in order of significance, are: solar collector area > heat pump unit capacity > thermal storage tank volume > solar collector installation angle. Compared to conventional full-factor orthogonal methods, the Taguchi approach reduced the number of orthogonal experiments while effectively predicting the optimal parameter combinations, thereby providing a more efficient, stable, and economical design solution for the coupled system. Based on the identified optimal parameter combinations, the system was optimized, resulting in an increase in the annual solar energy assurance rate from 19.52 % to 37.26 %. Furthermore, the annual operational energy consumption was reduced by 12.45 %, leading to an estimated annual cost savings of approximately 34,000 yuan. The findings of this study offer valuable reference for the design and optimization of multi-energy complementary hot water systems.